Resin composition containing methacrylic copolymer, molded article and film
Patent Information
- Application Number
- JP2020216755
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-12-25
Smart Images

Figure 0007638702000001 
Figure 0007638702000002 
Figure 0007638702000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a methacrylic resin composition, a molded article, and a film. [Background technology]
[0002] Methacrylic resins are excellent in transparency, weather resistance, surface hardness, etc. By molding a methacrylic resin composition containing the methacrylic resin, various components used for display components, electronic and electrical components, transportation components, etc. In recent years, there has been a demand for improved performance of various components, and in particular, there has been a strong demand for improved heat resistance.
[0003] For the purpose of improving heat resistance, a methacrylic resin composition having a ring structure in the main chain skeleton has been proposed. For example, Patent Document 1 discloses a modified methacrylic resin containing a structural unit derived from methyl methacrylate or the like and a structural unit having at least one ring structure selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, and an N-substituted or unsubstituted glutarimide unit in the main chain. In addition, Patent Document 2 discloses a copolymer consisting of a (meth)acrylic acid ester monomer unit, an unsaturated dicarboxylic anhydride monomer unit, and an unsaturated aromatic vinyl monomer unit.
[0004] Furthermore, since the methacrylic resin having high heat resistance has a relatively low strength and low toughness, there is concern about insufficient impact resistance of the molded product, and deterioration of productivity in terms of molding processability and handling of the film. A technique of incorporating an elastomer has been disclosed as a technique for improving the strength of heat-resistant methacrylic resin. Patent Document 3 discloses a technique of incorporating a crosslinked elastic body having a multilayer structure as an elastomer into a methacrylic resin containing a glutaric anhydride unit. Patent Document 4 discloses a technique of adding an acrylic rubber as an elastomer to a methacrylic resin containing a maleic anhydride unit. Furthermore, Patent Document 5 discloses a technique of adding a block copolymer containing a methacrylic acid ester polymer block and an acrylic acid ester polymer block as an elastomer to a methacrylic resin containing a structural unit having at least one ring structure selected from the group consisting of a lactone ring unit, a maleic anhydride unit, a glutaric anhydride unit, a glutarimide unit, an N-substituted maleimide unit, and a tetrahydropyran ring structural unit in the main chain. Patent Document 6 discloses a technique of adding a graft copolymer as an elastomer to a methacrylic resin having a glass transition temperature of 120°C or higher and a refractive index of 1.50 or higher, and describes an imidized resin of a methyl methacrylate-styrene copolymer as the methacrylic resin in the examples. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-179103 A [Patent Document 2] WO2014 / 021264 A1 [Patent Document 3] JP 2000-178399 A [Patent Document 4] Japanese Patent Application Publication No. 05-119217 [Patent Document 5] JP 2016-8225 A [Patent Document 6] JP 2009-203348 A Summary of the Invention [Problem to be solved by the invention]
[0006] In all of the disclosed techniques, the refractive index of the heat-resistant methacrylic resin having a ring structure in the main chain skeleton is high. Therefore, in order to maintain the inherent transparency of the methacrylic resin, it is necessary to design the refractive index of the elastomer contained therein to be as high as that of the acrylic resin in order to improve strength. However, increasing the refractive index of the elastomer by adjusting the molecular structure or the like can significantly impair flexibility and thermal decomposition resistance, and can cause a decrease in the toughness of the methacrylic resin containing the elastomer, poor appearance such as silver streaks, bubbles, coloring, and foreign matter in the molded product due to thermal decomposition, or a decrease in transparency.
[0007] In view of the above circumstances, an object of the present invention is to provide a methacrylic resin composition, a molded article, and a film that maintain transparency and heat resistance and have excellent rigidity, impact resistance, and thermal decomposition resistance. [Means for solving the problem]
[0008] As a result of investigations conducted in order to achieve the above object, the present invention has been completed, which includes the following aspects.
[0009] [1] A methacrylic resin composition comprising 51 to 99 mass% of a methacrylic copolymer (A) having 15 to 83 mass% of methyl methacrylate units, 7 to 35 mass% of α-methylstyrene units, 9.9 to 65 mass% of structural units (r) having at least two ring structures in the main chain selected from the group consisting of lactone ring units, glutaric anhydride units, N-substituted or unsubstituted glutarimide units, and N-substituted or unsubstituted maleimide units, 0.1 to 20 mass% of maleic anhydride units (m), and 0 to 20 mass% of other vinyl monomer units (c) copolymerizable with methyl methacrylate, and 1 to 49 mass% of an elastomer (B). [2] The methacrylic resin composition according to [1], wherein the structural unit (r) contains an N-substituted or unsubstituted glutarimide unit represented by formula (I).
[0010] [ka]
[0011] (In formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. [3] The methacrylic resin composition according to any one of [1] and [2], wherein the structural unit (r) contains an N-substituted or unsubstituted maleimide unit represented by formula (II).
[0012] [ka]
[0013] (In formula (II), R 3 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. [4] The methacrylic resin composition according to any one of [1] to [3], wherein the other vinyl monomer unit (c) copolymerizable with the methyl methacrylate unit is formed of at least one monomer selected from the group consisting of an acrylic acid ester monomer (c-1), an aromatic vinyl monomer (c-2), and a vinyl cyanide monomer (c-3). [5] The methacrylic resin composition according to any one of [1] to [4], wherein the other vinyl monomer unit (c) copolymerizable with the methyl methacrylate unit is formed of at least one selected from the group consisting of methyl acrylate, ethyl acrylate, styrene, and acrylonitrile. [6] The methacrylic resin composition according to any one of [1] to [5], wherein a mass ratio of the maleic anhydride unit (m) to a structural unit (r) having in its main chain at least two or more ring structures selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, an N-substituted or unsubstituted glutarimide unit, and an N-substituted or unsubstituted maleimide unit, {100×(m) / (r)}, is in the range of 5 to 50%. [7] The methacrylic resin composition according to any one of [1] to [6], wherein the refractive index of the methacrylic copolymer (A) is in the range of 1.500 to 1.540. [8] The methacrylic resin composition according to any one of [1] to [7], wherein the elastomer (B) contains a multilayer copolymer elastomer having a methacrylic acid ester unit and an acrylic acid ester unit. [9] The methacrylic resin composition according to any one of [1] to [8], wherein the average particle size of the multilayer copolymer elastomer is 0.15 μm or more and 1.0 μm or less.
[10] The methacrylic resin composition according to any one of [1] to [9], wherein a refractive index difference between the methacrylic copolymer (A) and the elastomer (B) is 0.01 or less.
[11] A molded article comprising the methacrylic resin composition according to any one of [1] to
[10] .
[12] A film comprising the methacrylic resin composition according to any one of [1] to
[10] .
[0014] According to the present invention, it is possible to obtain a molded article and a film which are highly transparent and heat resistant, free from defects in appearance, and excellent in impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The methacrylic resin composition of the present invention contains a methacrylic copolymer (A) and an elastomer (B). The content of the methacrylic copolymer (A) in the methacrylic resin composition is 51 to 99 mass%, preferably 55 to 95 mass%, and more preferably in the range of 60 to 90 mass%. When the content of the methacrylic copolymer (A) in the methacrylic resin composition of the present invention is 51 mass% or more, the composition has excellent heat resistance and surface hardness, and when the content is 99 mass% or less, the composition has improved brittleness.
[0016] (Methacrylic copolymer (A)) The methacrylic copolymer (A) according to the present invention contains methyl methacrylate units, α-methylstyrene units, structural units (r) and maleic anhydride (m).
[0017] The acrylic copolymer (A) according to the present invention has a ratio of methyl methacrylate units of 15 to 83 mass%, preferably 20 to 82 mass%, more preferably 25 to 80 mass%, based on the total structural units. If the ratio of methyl methacrylate units is less than this range, the total light transmittance of the resulting methacrylic copolymer is deteriorated, whereas if the ratio of methyl methacrylate units is more than this range, the heat resistance of the resulting acrylic copolymer is reduced.
[0018] The methacrylic copolymer (A) according to the present invention has an α-methylstyrene unit ratio of 7 to 35% by mass, preferably 8 to 30% by mass, more preferably 10 to 25% by mass, based on the total structural units. If the ratio of α-methylstyrene units is less than this range, the saturated water absorption of the resulting methacrylic copolymer will be high. In addition, a methacrylic copolymer having an α-methylstyrene unit ratio of more than 35% by mass will have low polymerizability and low productivity. In addition, it will inhibit the glutarimidization reaction caused by intramolecular cyclization of structural units derived from two adjacent (meth)acrylic acids, as described below.
[0019] The structural unit (r) is a structural unit having at least two ring structures in the main chain selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, an N-substituted or unsubstituted glutarimide unit, and an N-substituted or unsubstituted maleimide unit.
[0020] The methacrylic copolymer of the present invention may further contain, in the main chain, a methacrylamide unit represented by the following formula (Y) and / or a 2-(hydroxyalkyl)acrylic ester unit represented by the following formula (Z).
[0021] [ka]
[0022] (In the formula, R 4 , R 5 , R 6 is defined below) may also include
[0023] The structural unit (r) is preferably a structural unit having at least two ring structures selected from the group consisting of a glutaric anhydride unit, an N-substituted glutarimide unit, and an N-substituted maleimide unit in the main chain, and more preferably a structural unit having two ring structures, an N-substituted glutarimide unit and an N-substituted maleimide unit, in the main chain.
[0024] The lactone ring unit is a structural unit containing a >CH-OC(=O)- group in the ring structure. The structural unit containing a >CH-OC(=O)- group in the ring structure preferably has 4 to 8 ring constituent elements, more preferably 5 to 6, and most preferably 6. Examples of the structural unit containing a >CH-OC(=O)- group in the ring structure include lactone diyl structural units such as β-propiolactone diyl structural unit, γ-butyrolactone diyl structural unit, and δ-valerolactone diyl structural unit. The structural unit containing a >CH-OC(=O)- group in the ring structure can be obtained, for example, by intramolecular cyclization of a polymer having a hydroxy group and an ester group with the hydroxy group and the ester group. In addition, ">C" in the formula means that the carbon atom C has two bonds.
[0025] For example, an example of the δ-valerolactonediyl structural unit is a structural unit represented by the formula (IV).
[0026] [ka]
[0027] In formula (IV), R 7 , R 8 and R 9 are each independently a hydrogen atom or an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom or an organic group having 1 to 10 carbon atoms, more preferably a hydrogen atom or an organic group having 1 to 5 carbon atoms. Here, the organic group is not particularly limited as long as it has 1 to 20 carbon atoms, and examples thereof include a linear or branched alkyl group, a linear or branched aryl group, a -OCOCH3 group, and a -CN group. The organic group may contain a heteroatom such as an oxygen atom. R 7 and R 8 is preferably a methyl group, R 9 is preferably a hydrogen atom.
[0028] The lactone ring unit can be incorporated into the methacrylic copolymer by the methods described in JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, JP-A-2005-146084, etc., for example, by intramolecular cyclization of a structural unit derived from a 2-(hydroxyalkyl)acrylic acid ester and a structural unit derived from methyl (meth)acrylate.
[0029] The glutaric anhydride unit is a unit having a 2,6-dioxodihydropyrandiyl structure. An example of the unit having a 2,6-dioxodihydropyrandiyl structure is a structural unit represented by the formula (V).
[0030] [ka]
[0031] In formula (V), R 10 each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and is preferably a methyl group.
[0032] The unit having a 2,6-dioxodihydropyrandiyl structure can be incorporated into the methacrylic copolymer by the method described in JP 2007-197703 A, JP 2010-96919 A, or the like, for example, by intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid, or intramolecular cyclization of a structural unit derived from (meth)acrylic acid and a structural unit derived from methyl (meth)acrylate.
[0033] The N-substituted or unsubstituted glutarimide unit is a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure.
[0034] An example of a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure is a structural unit represented by formula (I).
[0035] [ka]
[0036] In formula (I), R 1 are each independently a hydrogen atom or a methyl group, and two R 1 Preferably, both R are methyl groups. 2 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group containing an aromatic ring and having 6 to 15 carbon atoms, preferably a hydrogen atom, a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, and more preferably a methyl group, an n-butyl group, or a cyclohexyl group.
[0037] The structural unit represented by formula (I) can be prepared by, for example, reacting the corresponding acid anhydride (IIa) with R 2 It may be produced by the reaction of an imidizing agent represented by NH2, or by the intramolecular cyclization reaction of a copolymer having a partial structure of formula (III). It is preferable to heat the copolymer to convert the structural unit represented by formula (III) to the structural unit represented by formula (I) by the intramolecular cyclization reaction.
[0038] Scheme (i)
[0039] [ka]
[0040] (In the formula, R 1 , R 2 is as defined above.)
[0041] The N-substituted or unsubstituted glutarimide unit can be obtained by the method described in WO2005 / 10838A1, JP2010-254742A, JP2008-273140A, JP2008-274187A, etc., specifically, by reacting a structural unit derived from two adjacent methyl methacrylates or a glutaric anhydride unit with an imidizing agent such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, etc., an aromatic hydrocarbon group-containing amine such as aniline, toluidine, trichloroaniline, etc., an alicyclic hydrocarbon group-containing amine such as cyclohexylamine, etc., urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, etc. Among these, methylamine is preferred. During this imidization reaction, some of the methyl methacrylate units may be hydrolyzed to form carboxyl groups, and it is preferable to return these carboxyl groups to the original methyl methacrylate units by an esterification reaction in which the esterification agent is used. The esterification agent is not particularly limited as long as it can exert the effects of the present invention, but dimethyl carbonate and trimethyl acetate can be preferably used. In addition to the esterification agent, a tertiary amine such as trimethylamine, triethylamine, or tributylamine can also be used as a catalyst.
[0042] The N-substituted or unsubstituted maleimide unit is a unit having an N-substituted or unsubstituted 2,5-pyrrolidinedione structure.
[0043] An example of the unit having an N-substituted or unsubstituted 2,5-pyrrolidinedione structure is a structural unit represented by formula (II).
[0044] [ka]
[0045] (In formula (II), R 3is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. The structural unit represented by formula (II) is a compound represented by the formula (II) consisting of maleic anhydride (M) and R 3 It is produced by the reaction of an imidizing agent represented by NH2.
[0046] The N-substituted or unsubstituted maleimide unit can be obtained by the method described in JP-B-61-026924, JP-B-7-042332, JP-A-9-100322, JP-A-2001-329021, etc., specifically, by reacting the maleic anhydride unit with an imidizing agent such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine or other aliphatic hydrocarbon group-containing amines, aniline, toluidine, trichloroaniline or other aromatic hydrocarbon group-containing amines, cyclohexylamine or other alicyclic hydrocarbon group-containing amines, urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea or other imidizing agent. Among these, methylamine is preferred.
[0047] The methacrylic copolymer according to the present invention has a ratio of the structural unit (r) of 9.9 to 65 mass%, preferably 10 to 62 mass%, more preferably 12 to 60 mass%, and further preferably 14 to 58 mass% based on the total structural units. As the content of the structural unit (R) increases, the thermal decomposition resistance of the methacrylic copolymer improves, but the melt viscosity increases and the moldability tends to decrease.
[0048] The methacrylic copolymer (A) according to the present invention has a ratio of maleic anhydride units (m) of 0.1 to 20% by mass, preferably 0.3 to 15% by mass, more preferably 0.5 to 10% by mass, and even more preferably 1 to 5% by mass, based on the total structural units. If the ratio of maleic anhydride units is less than this range, the heat resistance of the resulting methacrylic copolymer is low, and it is therefore necessary to increase the heat resistance by using other structural units such as α-methylstyrene units and structural units (r). The α-methylstyrene units and structural units (r) have a high refractive index, which causes the resulting methacrylic copolymer to have a high refractive index. In addition, a methacrylic copolymer having a ratio of maleic anhydride units (m) exceeding 20% by mass has a high saturated water absorption.
[0049] Examples of the other vinyl monomer units (c) copolymerizable with the methyl methacrylate unit (hereinafter, sometimes referred to as (c) monomer units) include acrylic ester monomer units (c-1), aromatic vinyl monomer units (c-2), vinyl cyanide monomer units (c-3), and other monomer units (c-4). The other vinyl monomer units (c) copolymerizable with the methyl methacrylate unit may be used alone or in combination of two or more.
[0050] The monomer unit (c) can be made of an appropriate material depending on the properties required for the methacrylic copolymer of the present invention. When properties such as thermal stability, fluidity, chemical resistance, optical properties, and compatibility with other resins are particularly required, at least one selected from the group consisting of an acrylic acid ester monomer unit, an aromatic vinyl monomer unit, and a vinyl cyanide monomer unit is suitable.
[0051] The acrylic acid ester monomer unit (c-1) constituting the methacrylic copolymer according to the present invention is not particularly limited, but from the viewpoints of heat resistance, fluidity, heat resistance stability, productivity, etc., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, benzyl acrylate, cyclohexyl acrylate, phenyl acrylate, etc. are preferred, more preferably methyl acrylate, ethyl acrylate, and n-butyl acrylate, and from the viewpoint of productivity, even more preferably methyl acrylate and ethyl acrylate.
[0052] The acrylic acid ester monomer unit (c-1) may be used alone or in combination of two or more kinds.
[0053] When the acrylic acid ester monomer unit (c-1) is used, its content is preferably 20% or less, more preferably 10% or less, based on all structural units, from the viewpoints of heat resistance and thermal stability.
[0054] The aromatic vinyl monomer unit (c-2) constituting the methacrylic copolymer according to the present invention is not particularly limited, but from the viewpoint of heat resistance, fluidity, heat stability, productivity, etc., styrene (St), o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylbenzylbenzene, isopropenylhexylbenzene, isopropenyloctylbenzene, etc. are preferred, and styrene is more preferred from the viewpoint of productivity.
[0055] The aromatic vinyl monomer unit (c-2) may be used alone or in combination of two or more kinds.
[0056] When the aromatic vinyl monomer unit (c-2) is used, its content is preferably 20% or less, more preferably 15% or less, based on all structural units, from the viewpoints of heat resistance and thermal stability.
[0057] The vinyl cyanide monomer unit (c-3) constituting the methacrylic copolymer according to the present invention is not particularly limited, but from the viewpoints of heat resistance, fluidity, heat stability, chemical resistance, productivity, etc., acrylonitrile (AN), methacrylonitrile, vinylidene cyanide, etc. are preferred, and among them, acrylonitrile is preferred from the viewpoints of availability and chemical resistance.
[0058] The vinyl cyanide monomer unit (c-3) may be used alone or in combination of two or more kinds.
[0059] When the vinyl cyanide monomer unit (c-3) is used, its content is preferably 20% or less, more preferably 10% or less, based on the total structural units, from the viewpoints of heat resistance and thermal stability.
[0060] The monomer constituting the monomer unit (c-4) other than (c-1) to (c-3) constituting the methacrylic copolymer according to the present invention is not particularly limited, but may be a monomer corresponding to the methacrylamide unit represented by formula (Y) or a monomer corresponding to the 2-(hydroxyalkyl)acrylic acid ester unit represented by formula (Z). For example, amides such as acrylamide and methacrylamide; ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, or both terminal hydroxyl groups of ethylene glycols or oligomers thereof esterified with acrylic acid or methacrylic acid; neopentyl glycol di(meth)acrylate, di(meth)acrylate, or two alcohol hydroxyl groups esterified with acrylic acid or methacrylic acid; trimethylolpropane, pentaerythritol, or other polyhydric alcohol derivatives esterified with acrylic acid or methacrylic acid; and polyfunctional monomers such as divinylbenzene.
[0061] Among the monomers constituting the above-mentioned (c) monomer unit, at least one selected from the group consisting of methyl acrylate (MA), ethyl acrylate, styrene, and acrylonitrile is preferred from the viewpoint of availability.
[0062] In the methacrylic copolymer of the present invention, the ratio of other vinyl monomer units (c) copolymerizable with methyl methacrylate units is preferably 0 to 20% by mass, more preferably 0 to 15% by mass, and even more preferably 0 to 10% by mass, based on the total structural units. A methacrylic copolymer having a ratio of other vinyl monomer units (c) copolymerizable with methyl methacrylate units exceeding 20% by mass has reduced heat resistance and rigidity. The ratios of methyl methacrylate units, α-methylstyrene units, maleic anhydride units (m), structural units (r), and monomer units (c) are as follows: 1 H-NMR, 13 It can be measured by C-NMR, etc.
[0063] From the viewpoint of heat resistance and warm water resistance, the methacrylic copolymer of the present invention preferably has a mass ratio, {100×(m) / (r)}, of maleic anhydride units (m) to structural units (r) having in the main chain at least two ring structures selected from the group consisting of lactone ring units, glutaric anhydride units, and N-substituted or unsubstituted glutarimide units, in the range of 5 to 50% and more preferably 10 to 30% by mass.
[0064] The methacrylic copolymer (A) according to the present invention has a weight average molecular weight (Mw) of preferably 40,000 to 200,000, more preferably 50,000 to 180,000, and further preferably 55,000 to 160,000. When Mw is 40,000 or more, the strength, toughness, etc. of the molded article of the present invention are improved. When Mw is 200,000 or less, the flowability of the methacrylic copolymer is improved, and molding processability is improved.
[0065] The weight average molecular weight (Mw) is a value calculated by converting a chromatogram measured by gel permeation chromatography into the molecular weight of standard polystyrene.
[0066] The methacrylic copolymer (A) according to the present invention has an acid value of preferably 0.01 to 0.30 mmol / g, more preferably 0.05 to 0.28 mmol / g. The acid value is a value proportional to the content of carboxylic acid units and carboxylic anhydride units in the methacrylic copolymer. The acid value can be calculated, for example, by the method described in JP-A-2005-23272. When the acid value is within the above range, the balance of heat resistance, mechanical properties, and moldability is excellent.
[0067] The methacrylic copolymer (A) according to the present invention has a glass transition temperature of preferably 130°C as a lower limit, more preferably 131°C, and even more preferably 132°C as an upper limit, and is not particularly limited, but is preferably 170°C.
[0068] In this specification, the "glass transition temperature (Tg)" is measured in accordance with JIS K7121. Specifically, the temperature is raised once to 230°C, then cooled to room temperature, and then the DSC curve is measured under conditions of raising the temperature from room temperature to 230°C at a rate of 10°C / min. The midpoint determined from the DSC curve measured during the second heating is determined as the "glass transition temperature (Tg)".
[0069] The saturated water absorption of the methacrylic copolymer (A) according to the present invention is measured under the following conditions. The methacrylic copolymer is press-molded into a sheet having a thickness of 1.0 mm. A test piece of 50 mm x 50 mm is cut out from the center of the obtained press-molded sheet and dried in a dryer at 80 ° C for 16 hours or more. The dried test piece is cooled to room temperature in a desiccator, and then its weight is measured to the nearest 0.1 mg, and this weight is defined as the initial weight Wo. The test piece is immersed in distilled water at 23 ° C., and after immersion for 24 hours, the test piece is removed from the water and all surface moisture is wiped off with a clean, dry cloth or filter paper. Within 1 minute of removing from the water, the test piece is weighed again to the nearest 0.1 mg. The test piece is immersed again, and after 24 hours, its weight is measured again in the same manner as above. The weight at which the weight change rate of the test piece becomes within 0.02% of Wo is defined as the saturated weight Ws. The saturated water absorption was calculated using equation (2).
[0070]
number
[0071] The saturated water absorption is preferably 2.5% or less, more preferably 2.1% or less, and further preferably 2.0% or less.
[0072] The methacrylic copolymer (A) according to the present invention has a 1% thermal weight loss temperature in a nitrogen atmosphere of preferably 300° C. or higher, more preferably 310° C. or higher. The 1% thermal weight loss temperature can be measured using a thermogravimetric analyzer (TGA). The 1% thermal weight loss temperature can be determined as the temperature at which the weight loss is 1% relative to the charged weight.
[0073] The refractive index of the methacrylic copolymer (A) according to the present invention is preferably 1.500 to 1.540, more preferably 1.505 to 1.535. When the refractive index is within this range, the transparency of the methacrylic resin composition is high. In this specification, the "refractive index" refers to a value measured at a measurement wavelength of 587.6 mm (D line) as described in the examples below.
[0074] The methacrylic copolymer (A) according to the present invention can be obtained by a method including subjecting a copolymer (hereinafter sometimes referred to as a precursor polymer) of methyl methacrylate (MMA), α-methylstyrene (αMSt), maleic anhydride (Mah), and optionally other vinyl monomers, to a ring structure-forming reaction.
[0075] That is, the production method includes the steps of continuously supplying a reaction raw material containing a monomer mixture containing 50 to 92 mass % of methyl methacrylate, 30 to 7 mass % of α-methylstyrene, 1 to 20 mass % of maleic anhydride and 0 to 20 mass % of other copolymerizable vinyl monomers, a radical polymerization initiator, and optionally a chain transfer agent, to a tank-type reactor; The process includes a step of bulk polymerizing the monomer mixture in a tank reactor to a polymerization conversion rate of 30 to 60 mass% to obtain a reaction product, a step of removing the monomer mixture in the reaction product to obtain a precursor polymer, and a step of subjecting the obtained precursor polymer to a ring structure-forming reaction, and each step can be carried out by a known technique.
[0076] The ring structure forming reaction can be carried out, for example, using an extruder. Examples of the extruder include a single screw extruder, a twin screw extruder, and a multi-screw extruder. In terms of mixing performance, a twin screw extruder is preferred. Twin screw extruders include non-intermeshing co-rotating, intermeshing co-rotating, non-intermeshing counter-rotating, and intermeshing counter-rotating. Intermeshing co-rotating extruders are preferred because they can rotate at high speeds and can efficiently promote mixing. These extruders may be used alone or in series.
[0077] In the ring structure forming reaction using an extruder, for example, a precursor polymer as a raw material is charged from the raw material charging section of the extruder, the precursor polymer is melted, and the cylinder is filled with the precursor polymer. Then, an imidizing agent (optional component) and the like are injected into the extruder using an addition pump, whereby the ring structure forming reaction can be progressed in the extruder. When an imidizing agent is used, the structural unit (R) contains an N-substituted or unsubstituted glutarimide unit, and may contain a lactone ring unit and / or a glutaric anhydride unit as necessary. A preferred imidizing agent is R 2 -NH2(R 2 is as defined above). The imidizing agent is preferably used in an amount of 1.6 to 12 parts by mass per 100 parts by mass of the methacrylic copolymer. When the amount of the imidizing agent used is within the above range, the by-production of methacrylic acid amide units can be suppressed.
[0078] The resin temperature in the reaction zone in the extruder is preferably in the range of 180 to 280°C, more preferably in the range of 200 to 280°C. If the resin temperature in the reaction zone is less than 180°C, the heat resistance of the methacrylic copolymer tends to decrease due to a decrease in the reaction efficiency of the ring structure formation reaction, the by-production of methacrylamide units, etc. If the resin temperature in the reaction zone exceeds 280°C, the resin decomposition becomes significant, and the mechanical strength, such as the tensile breaking strength, of the molded body and film made of the obtained methacrylic copolymer tends to decrease. The reaction zone in the extruder refers to the region between the injection position of the imidizing agent, etc., in the cylinder of the extruder to the resin discharge port (die part).
[0079] By increasing the reaction time in the reaction zone of the extruder, the ring structure forming reaction can be promoted. The reaction time in the reaction zone of the extruder is preferably longer than 10 seconds, and more preferably longer than 30 seconds. If the reaction time is less than 10 seconds, the ring structure forming reaction may hardly proceed.
[0080] The resin pressure in the extruder is preferably in the range of atmospheric pressure to 50 MPa, and more preferably in the range of 1 to 30 MPa. If it is 50 MPa or more, it exceeds the limit of the mechanical pressure resistance of a normal extruder, and a special device is required, which is not preferable from the viewpoint of cost.
[0081] It is preferable to use an extruder having a vent hole that can reduce the pressure to below atmospheric pressure. With such a configuration, unreacted materials, by-products such as methanol, and monomers can be removed, and the breaking strength of a molded article containing the methacrylic resin composition of the present invention tends to be improved.
[0082] During the ring structure forming reaction, a carboxyl group may be by-produced in the methacrylic copolymer. This carboxyl group may be converted to an ester group by an esterifying agent or a catalyst, if necessary. This can reduce foaming of the resin during the production of an optical film. The ester group varies depending on the esterifying agent and catalyst used, but from the viewpoints of reducing the resin melt viscosity during melt molding, the reactivity of esterification, and the heat resistance of the resin after esterification, it is preferable that the ester group contains a methyl methacrylate unit, and more preferably contains both a methyl methacrylate unit and an ethyl methacrylate unit.
[0083] As the esterifying agent, dimethyl carbonate is preferred from the viewpoints of cost, reactivity, etc.
[0084] (Elastomer (B)) The content of the elastomer (B) in the methacrylic resin composition of the present invention is 1 to 49 mass%, preferably 5 to 45 mass%, and more preferably 10 to 40 mass%. The brittleness of the acrylic resin composition of the present invention is improved by having the content of the elastomer (B) in the range of 1 to 49 mass%.
[0085] The elastomer (B) used in the present invention is not particularly limited as long as it can be kneaded with the methacrylic copolymer (A) to obtain a resin composition. The elastomer (B) is preferably one that forms a dispersed phase in the resin composition. The shape of the dispersed phase is not particularly limited, and examples thereof include spherical, ellipsoidal, rod-like, flat, and string-like shapes.
[0086] The elastomer (B) preferably has an acrylic acid ester unit. Examples of the acrylic acid ester include alkyl acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate; aryl acrylates such as phenyl acrylate, benzyl acrylate, paracumylphenol ethylene oxide modified acrylate, and o-phenylphenol ethylene oxide modified acrylate; and cycloalkyl acrylates such as cyclohexyl acrylate and norbornenyl acrylate. Among these, alkyl acrylates and aryl acrylates are preferred, alkyl acrylates are more preferred, and butyl acrylate is the most preferred. The amount of acrylic acid ester units in the elastomer (B) is preferably 30% by mass or more, more preferably 35% by mass or more and 90% by mass or less, and even more preferably 40% by mass or more and 80% by mass or less.
[0087] The elastomer (B) may have a vinyl monomer unit having only one polymerizable carbon-carbon double bond in one molecule in addition to the acrylic ester unit. Examples of the vinyl monomer include methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, and 2-ethylhexyl methacrylate; methacrylic acid aryl esters such as phenyl methacrylate and benzyl methacrylate; methacrylic acid cycloalkyl esters such as cyclohexyl methacrylate and norbornenyl methacrylate; aromatic vinyl compounds such as styrene and α-methylstyrene; acrylamide; methacrylamide; acrylonitrile; and methacrylonitrile.
[0088] The elastomer (B) may further contain conjugated diene monomer units, such as those containing 1,3-butadiene, isoprene, or both of these units.
[0089] The elastomer (B) is not particularly limited by its molecular form, and examples thereof include linear polymer elastomers, branched polymer elastomers, multilayer copolymer elastomers, and block copolymer elastomers. Of these, the elastomer (B) is preferably one containing a multilayer copolymer elastomer having methacrylic acid ester units and acrylic acid ester units, or one containing a block copolymer elastomer consisting of a polymer block (b1) mainly having methacrylic acid ester units and a polymer block (b2) having acrylic acid ester units. The elastomer (B) may contain a combination of a block copolymer elastomer and a multilayer copolymer elastomer.
[0090] The multilayer copolymer elastomer may be a particle including an outermost layer made of a thermoplastic polymer (P) and an inner layer made of a crosslinked polymer that is in contact with and covered by the outermost layer, and it is preferable that the inner layer and the outermost layer form a core and a shell. The multilayer copolymer elastomer may be, for example, a two-layer polymer elastomer particle having a core (inner layer) of a crosslinked rubber polymer (Q) and an outer shell (outermost layer) of a thermoplastic polymer (P), a three-layer polymer elastomer particle having a core (inner layer) of a crosslinked polymer (R) and an inner shell (inner layer) of a crosslinked rubber polymer (Q) and an outer shell (outermost layer) of a thermoplastic polymer (P), or a four-layer polymer elastomer particle having a core (inner layer) of a crosslinked rubber polymer (Q) and a first inner shell (inner layer) of a crosslinked polymer (R) and a second inner shell (inner layer) of a crosslinked rubber polymer (Q) and an outer shell (outermost layer) of a thermoplastic polymer (P).
[0091] From the viewpoint of transparency, it is preferable to select the polymers contained in each layer so that the difference in refractive index between adjacent layers is preferably less than 0.005, more preferably less than 0.004, and even more preferably less than 0.003.
[0092] The mass ratio of the inner layer to the outermost layer in the multilayer copolymer elastomer is preferably 60 / 40 to 95 / 5, more preferably 70 / 30 to 90 / 10. The inner layer may include all layers except the outermost layer. The proportion of the layer containing the crosslinked rubber polymer (Q) in the inner layer is preferably 20 to 70 mass%, more preferably 30 to 50 mass%.
[0093] The multilayer copolymer elastomer has an average particle size of preferably 0.1 to 1.0 μm, more preferably 0.16 to 0.8 μm, and even more preferably 0.18 to 0.5 μm. By using a multilayer copolymer elastomer having an average particle size within such range, particularly an average particle size of 0.15 to 1.0 μm, toughness can be exhibited even with a small amount of the elastomer, and therefore rigidity and weather resistance are not impaired. In this specification, the average particle size is the average value in the volume-based particle size distribution measured by a light scattering method.
[0094] The thermoplastic polymer (P) is a polymer comprising methacrylic acid alkyl ester units having an alkyl group having 1 to 8 carbon atoms and, if necessary, monofunctional monomer units other than the methacrylic acid alkyl esters. It is preferable that the thermoplastic polymer (P) does not contain polyfunctional monomer units.
[0095] The amount of the methacrylic acid alkyl ester units having an alkyl group having 1 to 8 carbon atoms constituting the thermoplastic polymer (P) is preferably 80 to 100 mass %, more preferably 85 to 95 mass %, based on the mass of the thermoplastic polymer (P).
[0096] Methacrylic acid alkyl esters having an alkyl group with 1 to 8 carbon atoms (hereinafter referred to as methacrylic acid C 1-8 A preferred example of the alkyl ester is methyl methacrylate.
[0097] Methacrylic acid C that constitutes the thermoplastic polymer (P) 1-8The amount of the monofunctional monomer units other than the alkyl ester is preferably from 0 to 70% by mass, more preferably from 5 to 65% by mass, based on the mass of the thermoplastic polymer (P).
[0098] Methacrylic acid C 1-8 Examples of monofunctional monomers other than alkyl esters include aryl methacrylate esters such as phenyl methacrylate and benzyl methacrylate, acrylic esters such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate and propyl acrylate, and aromatic vinyl compounds such as styrene.
[0099] The outermost layer may be a single layer made of one kind of thermoplastic polymer (P), or may be a multilayer made of two or more kinds of thermoplastic polymers (P).
[0100] The amount of the thermoplastic polymer (P) is preferably 15 to 75% by mass, more preferably 45 to 70% by mass, and further preferably 50 to 65% by mass, based on the amount of the multilayer copolymer elastomer.
[0101] The layer of crosslinked elastic material which is the inner layer has an intermediate layer made of a crosslinked rubber polymer (Q) and an inner layer made of a crosslinked polymer (R) which is in contact with and covers the intermediate layer.
[0102] The crosslinked polymer (R) is composed of methyl methacrylate units, monofunctional monomer units other than methyl methacrylate, and polyfunctional monomer units.
[0103] The amount of methyl methacrylate units constituting the crosslinked polymer (R) is preferably 40 to 98.5% by mass, more preferably 45 to 95% by mass, based on the mass of the crosslinked polymer (R).
[0104] The amount of the monofunctional monomer units other than methyl methacrylate constituting the crosslinked polymer (R) is 5 to 60% by mass, preferably 10 to 50% by mass, based on the mass of the crosslinked polymer (R).
[0105] Examples of monofunctional monomers other than methyl methacrylate include acrylic esters such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and propyl acrylate; aryl acrylates such as phenyl acrylate, benzyl acrylate, para-cumylphenol ethylene oxide modified acrylate, and o-phenylphenol ethylene oxide modified acrylate; and aromatic vinyl compounds such as styrene.
[0106] The amount of the polyfunctional monomer unit constituting the crosslinked polymer (R) is preferably 0.05 to 0.4 mass %, more preferably 0.1 to 0.3 mass %, based on the mass of the crosslinked polymer (R).
[0107] Examples of the polyfunctional monomer include ethylene glycol dimethacrylate, propylene glycol dimethacrylate, triethylene glycol dimethacrylate, hexanediol dimethacrylate, ethylene glycol diacrylate, propylene glycol diacrylate, triethylene glycol diacrylate, allyl methacrylate, triallyl isocyanurate, and divinylbenzene.
[0108] The amount of the crosslinked polymer (R) is preferably 5 to 40% by mass, more preferably 7 to 38% by mass, and further preferably 10 to 35% by mass, based on the amount of the multilayer copolymer elastomer.
[0109] The crosslinked rubber polymer (Q) contains acrylate alkyl ester units having an alkyl group having 1 to 8 carbon atoms, acrylate aryl ester units and / or conjugated diene units, and polyfunctional monomer units.
[0110] The amount of the acrylic acid alkyl ester units and / or conjugated diene units having an alkyl group having 1 to 8 carbon atoms constituting the crosslinked rubber polymer (Q) is preferably 85 to 99.5 mass %, more preferably 95 to 99 mass %, based on the mass of the crosslinked rubber polymer (Q).
[0111] Examples of the alkyl acrylate ester having an alkyl group having 1 to 8 carbon atoms include methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and propyl acrylate.
[0112] Examples of the aryl acrylate include aryl acrylate such as phenyl acrylate, benzyl acrylate, paracumylphenol ethylene oxide modified acrylate, and o-phenylphenol ethylene oxide modified acrylate.
[0113] Examples of conjugated dienes include 1,3-butadiene and isoprene.
[0114] Examples of the crosslinked rubber polymer (Q) containing 1,3-butadiene as a monomer include 1,3 polybutadiene homopolymers and copolymers composed of 50% by weight or more of 1,3-polybutadiene units. Examples of such copolymers include butadiene-aromatic vinyl compound copolymers such as butadiene-styrene copolymers and butadiene-vinyltoluene copolymers, and further include terpolymers composed of 50% by weight or more of 1,3-butadiene units. These can usually be easily produced by known emulsion polymerization.
[0115] The amount of the polyfunctional monomer unit constituting the crosslinked rubber polymer (Q) is preferably 1 to 1.7 mass %, more preferably 1.2 to 1.6 mass %, and further preferably 1.3 to 1.5 mass %, based on the mass of the crosslinked rubber polymer (Q).
[0116] As the polyfunctional monomer, those exemplified for the crosslinked polymer (R) can be mentioned.
[0117] From the viewpoint of improving flex resistance, the ratio of the mass of the polyfunctional monomer unit in the crosslinked polymer (R) to the mass of the polyfunctional monomer unit in the crosslinked rubber polymer (Q) is preferably 0.05 to 0.25, more preferably 0.1 to 0.2. The glass transition temperature of the crosslinked rubber polymer (Q) is preferably lower than the glass transition temperature of the crosslinked polymer (R).
[0118] The amount of the crosslinked rubber polymer (Q) is preferably 20 to 55% by mass, more preferably 25 to 50% by mass, and further preferably 30 to 45% by mass, based on the amount of the multilayer copolymer elastomer.
[0119] The multilayer copolymer elastomer has an average diameter (d) of the crosslinked elastic layer of preferably 60 to 110 nm, more preferably 65 to 105 nm, and even more preferably 70 to 100 nm. The average diameter d (nm) of the crosslinked elastic layer can be measured as follows. A resin composition containing the multilayer copolymer elastomer is molded using a hydraulic press molding machine with a mold size of 50 mm x 120 mm, a press temperature of 250°C, a preheating time of 3 minutes, and a press pressure of 50 kg / cm. 2 , press time 30 seconds, cooling temperature 20℃, cooling pressure 50kg / cm 2 The plate is molded into a 3 m plate under the conditions of 10 minutes cooling time. The plate obtained is cut in a direction parallel to the long side at -100°C using a microtome to obtain a 40 nm thick slice, which is then stained with ruthenium. The stained slice is observed and photographed using a scanning transmission electron microscope (JEOL JSM7600F) at an accelerating voltage of 25 kV. The short and long diameters of the ruthenium-stained portion (exposed portion of the cross-linked elastic layer) are measured, and (short diameter + long diameter) / 2 is defined as the diameter of the cross-linked elastic layer. After measuring 20 or more pieces, the number average value (average diameter) is calculated.
[0120] The refractive index of the multilayer copolymer elastomer is preferably 1.500 to 1.540, and more preferably 1.505 to 1.535. When the refractive index is within this range, the transparency of the methacrylic resin composition is high.
[0121] The glass transition temperature of the crosslinked rubber polymer (Q) of the multilayer copolymer elastomer is preferably 23° C. or lower, more preferably 10° C. or lower, and even more preferably 0° C. or lower. A glass transition temperature above 23° C. is not preferred because toughness is impaired.
[0122] The multi-layer copolymer elastomer may be produced by any method, including, for example, emulsion polymerization.
[0123] In the case of emulsion polymerization, for example, a monomer (r) for constituting a crosslinked polymer (R) is emulsion-polymerized to obtain a latex containing the crosslinked polymer (R), a monomer (q) for constituting a crosslinked rubber polymer (Q) is added thereto, and the monomer (q) is seed-emulsion-polymerized to obtain a latex containing the crosslinked polymer (R) and the crosslinked rubber polymer (q), and a monomer (p) for constituting a thermoplastic polymer (P) is added thereto, and the monomer (p) is seed-emulsion-polymerized to obtain a latex containing a multilayer copolymer elastomer. Incidentally, emulsion polymerization is a known method used to obtain a latex containing a polymer. Seed emulsion polymerization is a method in which a polymerization reaction of a monomer is carried out on the surface of a seed particle. Seed emulsion polymerization is preferably used to obtain a core-shell structure polymer particle.
[0124] (Methacrylic resin composition) In the methacrylic resin composition of the present invention, the mass ratio of the methacrylic copolymer (A) / the elastomer (B) is from 99 / 1 to 51 / 49, preferably from 95 / 5 to 55 / 45, and more preferably from 90 / 10 to 60 / 40, from the viewpoints of impact resistance and surface hardness.
[0125] In the methacrylic resin composition of the present invention, the absolute value of the refractive index difference between the methacrylic copolymer (A) and the elastomer (B) is preferably 0.01 or less, more preferably 0.008 or less, and even more preferably 0.005 or less. When the absolute value of the refractive index difference between the methacrylic copolymer (A) and the elastomer (B) is 0.01 or less, it is possible to obtain a methacrylic resin composition having excellent transparency.
[0126] Methods for satisfying the above refractive index conditions include a method for adjusting the unit composition ratio of each monomer in the methacrylic copolymer (A) and / or a method for adjusting the composition ratio of the polymer or monomer used in the elastomer (B).
[0127] The methacrylic resin composition of the present invention has a softening temperature of a molded article measured by the method specified in JIS K7206 B50 method of preferably 100° C. or higher, more preferably 105° C. or higher, and even more preferably 110° C. or higher. When the softening temperature is 110° C. or higher, the molded article has excellent heat resistance and excellent dimensional stability at high temperatures.
[0128] The methacrylic resin composition of the present invention has a saturated water absorption of 3.5% or less, more preferably 3.3% or less, and even more preferably 3.0% or less, measured under the same conditions as those for the saturated water absorption of the methacrylic copolymer (A). The saturated water absorption of 3.5% or less reduces the effect of deterioration of physical properties due to moisture absorption, and the dimensional stability at high humidity is excellent.
[0129] The methacrylic resin composition of the present invention may contain a filler as necessary within a range that does not impair the effects of the present invention. Examples of the filler include calcium carbonate, talc, carbon black, titanium oxide, silica, clay, barium sulfate, magnesium carbonate, etc. The amount of the filler that can be contained in the resin composition of the present invention is preferably 3 mass% or less, more preferably 1.5 mass% or less.
[0130] The methacrylic resin composition of the present invention may contain other polymers as long as the effects of the present invention are not impaired. Examples of other polymers include polyolefin resins such as polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene; ethylene-based ionomers; styrene-based resins such as polystyrene, styrene-maleic anhydride copolymer, high impact polystyrene, AS resin, ABS resin, AES resin, AAS resin, ACS resin, and MBS resin; methyl methacrylate-based polymers other than the acrylic copolymer (A), and methyl methacrylate-styrene copolymers; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; polyamides such as nylon 6, nylon 66, and polyamide elastomers; polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymers, polyacetal, polyvinylidene fluoride, polyurethane, phenoxy resins, modified polyphenylene ethers, polyphenylene sulfide, and silicone-modified resins; silicone rubber; styrene-based thermoplastic elastomers such as SEPS, SEBS, and SIS; and olefin-based rubbers such as IR, EPR, and EPDM. The amount of other polymers that can be contained in the resin composition of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, and most preferably 0% by mass.
[0131] The methacrylic resin composition of the present invention may contain additives such as antioxidants, heat deterioration inhibitors, ultraviolet absorbers, light stabilizers, lubricants, release agents, polymer processing aids, antistatic agents, flame retardants, dyes and pigments, light diffusing agents, organic dyes, matting agents, and fluorescent materials, as long as the effects of the present invention are not impaired.
[0132] The antioxidant is effective in preventing the oxidative deterioration of the resin by itself in the presence of oxygen. Examples of the antioxidant include phosphorus-based antioxidants, hindered phenol-based antioxidants, and thioether-based antioxidants. These antioxidants can be used alone or in combination of two or more. Among these, from the viewpoint of the effect of preventing the deterioration of optical properties due to coloring, phosphorus-based antioxidants and hindered phenol-based antioxidants are preferred, and the combined use of a phosphorus-based antioxidant and a hindered phenol-based antioxidant is more preferred.
[0133] When the phosphorus-based antioxidant and the hindered phenol-based antioxidant are used in combination, their ratio is not particularly limited, but the mass ratio of the phosphorus-based antioxidant / the hindered phenol-based antioxidant is preferably 1 / 5 to 2 / 1, and more preferably 1 / 2 to 1 / 1.
[0134] Examples of phosphorus-based antioxidants include 2,2-methylenebis(4,6-di-t-butylphenyl)octyl phosphite (manufactured by ADEKA Corporation; trade name: Adeka STAB HP-10), tris(2,4-di-t-butylphenyl)phosphite (manufactured by Ciba Specialty Chemicals Corporation; trade name: IRUGA FOS 168), and 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (manufactured by ADEKA Corporation; trade name: Adeka STAB PEP-36).
[0135] Examples of the hindered phenol antioxidant include pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (manufactured by Ciba Specialty Chemicals; trade name IRGANOX1010) and octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (manufactured by Ciba Specialty Chemicals; trade name IRGANOX1076).
[0136] The thermal degradation inhibitor is a compound that can prevent thermal degradation of a resin by capturing polymer radicals that are generated when the resin is exposed to high heat in a substantially oxygen-free state. Examples of the thermal degradation inhibitor include 2-t-butyl-6-(3'-t-butyl-5'-methyl-hydroxybenzyl)-4-methylphenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GM) and 2,4-di-t-amyl-6-(3',5'-di-t-amyl-2'-hydroxy-α-methylbenzyl)phenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GS).
[0137] An ultraviolet absorber is a compound that has the ability to absorb ultraviolet rays. An ultraviolet absorber is a compound that is said to have the function of converting light energy into heat energy.
[0138] Examples of ultraviolet absorbents include benzophenones, benzotriazoles, triazines, benzoates, salicylates, cyanoacrylates, oxalic anilides, malonic acid esters, and formamidines. These may be used alone or in combination of two or more. Among these, benzotriazoles, triazines, or compounds having a maximum molar absorption coefficient εmax of 1200 dm at a wavelength of 380 to 450 nm are particularly preferred. 3 mol -1 cm -1 Preferred are UV absorbers which are:
[0139] Light stabilizers are compounds that are said to have the function of capturing radicals generated mainly by oxidation due to light, and examples thereof include hindered amines such as compounds having a 2,2,6,6-tetraalkylpiperidine skeleton.
[0140] Examples of the lubricant include stearic acid, behenic acid, stearamide acid, methylene bisstearamide, hydroxystearic acid triglyceride, paraffin wax, ketone wax, octyl alcohol, and hardened oil.
[0141] The mold release agent is a compound having a function of facilitating the release of a molded product from a mold, and examples thereof include higher alcohols such as cetyl alcohol and stearyl alcohol, and higher fatty acid esters of glycerin such as monoglyceride stearate and diglyceride stearate. The use of higher fatty acid esters of glycerin may cause gel-like foreign matter, so it is preferable to use higher alcohols.
[0142] The polymer processing aid is a compound that is effective in achieving thickness accuracy and thinning when molding an acrylic resin composition. The polymer processing aid can usually be produced by an emulsion polymerization method. The polymer processing aid is preferably a polymer particle having a particle size of 0.05 to 0.5 μm.
[0143] The polymer particles may be single-layer particles made of a polymer with a single composition ratio and a single intrinsic viscosity, or may be multi-layer particles made of two or more polymers with different composition ratios or intrinsic viscosities. Among these, preferred are particles with a two-layer structure having a polymer layer with a low intrinsic viscosity in the inner layer and a polymer layer with a high intrinsic viscosity of 5 dl / g or more in the outer layer. The polymer processing aid preferably has an intrinsic viscosity of 3 to 6 dl / g. If the intrinsic viscosity is too low, the effect of improving moldability is low. If the intrinsic viscosity is too high, the melt flowability of the acrylic resin composition is likely to decrease.
[0144] Examples of the antistatic agent include alkylsulfonates such as sodium heptyl sulfonate, sodium octyl sulfonate, sodium nonyl sulfonate, sodium decyl sulfonate, sodium dodecyl sulfonate, sodium cetyl sulfonate, sodium octadecyl sulfonate, sodium diheptyl sulfonate, potassium heptyl sulfonate, potassium octyl sulfonate, potassium nonyl sulfonate, potassium decyl sulfonate, potassium dodecyl sulfonate, potassium cetyl sulfonate, potassium octadecyl sulfonate, potassium diheptyl sulfonate, lithium heptyl sulfonate, lithium octyl sulfonate, lithium nonyl sulfonate, lithium decyl sulfonate, lithium dodecyl sulfonate, lithium cetyl sulfonate, lithium octadecyl sulfonate, and lithium diheptyl sulfonate.
[0145] Examples of the flame retardant include metal hydrates having a hydroxyl group or crystal water, such as magnesium hydroxide, aluminum hydroxide, hydrated aluminum silicate, hydrated magnesium silicate, and hydrotalcite; phosphate compounds, such as polyamine phosphoric acid esters; and silicon compounds. Of these, preferred are phosphate ester-based flame retardants, such as trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, tricyclohexyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, dimethylethyl phosphate, methyl dibutyl phosphate, ethyl dipropyl phosphate, and hydroxyphenyl diphenyl phosphate.
[0146] Examples of dyes and pigments include red organic pigments such as Para Red, Fire Red, Pyrazolone Red, Thioindigo Red, and Perylene Red; blue organic pigments such as Cyanine Blue and Indanthrene Blue; and green organic pigments such as Cyanine Green and Naphthol Green. One or more of these can be used.
[0147] As the organic dye, a compound having a function of converting ultraviolet light into visible light is preferably used.
[0148] Examples of the light diffusing agent and the matting agent include glass particles, polysiloxane-based crosslinked particles, crosslinked polymer particles, talc, calcium carbonate, and barium sulfate.
[0149] Examples of fluorescent materials include fluorescent pigments, fluorescent dyes, fluorescent white dyes, fluorescent brighteners, and fluorescent bleaches.
[0150] These additives may be used alone or in combination of two or more. These additives may be added to the polymerization reaction solution when producing the methacrylic copolymer (A) and elastomer (B), or may be added to the produced methacrylic copolymer (A) and elastomer (B), or may be added when preparing the methacrylic resin composition of the present invention. The total amount of additives contained in the methacrylic resin composition of the present invention is preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less, based on the methacrylic resin composition, from the viewpoint of suppressing defective appearance of the molded article.
[0151] The method for preparing the methacrylic resin composition of the present invention is not particularly limited. For example, a method of polymerizing a monomer mixture containing methyl methacrylate or the like in the presence of an elastomer (B) to produce an acrylic copolymer (A), or a method of melt-kneading the methacrylic copolymer (A) and the elastomer (B) can be mentioned. During melt-kneading, other polymers and additives may be mixed as necessary, the methacrylic copolymer (A) may be mixed with other polymers and additives and then mixed with the elastomer (B), the elastomer (B) may be mixed with other polymers and additives and then mixed with the methacrylic copolymer (A), or other methods may be used. Kneading can be performed using a known mixing or kneading device such as a kneader-ruder, an extruder, a mixing roll, or a Banbury mixer. Of these, a twin-screw extruder is preferred.
[0152] The acrylic resin composition of the present invention can be made into a form such as pellets in order to enhance convenience during storage, transportation, or molding.
[0153] (Molded body) The molded article of the present invention is made of the acrylic resin composition of the present invention. The manufacturing method of the molded article of the present invention is not particularly limited. For example, melt molding methods such as the T-die method (lamination method, co-extrusion method, etc.), inflation method (co-extrusion method, etc.), compression molding method, blow molding method, calendar molding method, vacuum molding method, injection molding method (insert method, two-color method, press method, core-back method, sandwich method, etc.), and solution casting method can be mentioned. Among these, the T-die method, inflation method, and injection molding method are preferred from the viewpoint of high productivity, cost, etc. There is no limitation on the type of molded article, but films (planar molded articles having a thickness of 5 μm to 250 μm) and sheets (planar molded articles thicker than 250 μm) are preferred, and among them, films are particularly preferred.
[0154] The film, which is one form of the molded article of the present invention, can be produced by a solution casting method, a melt casting method, an extrusion molding method, an inflation molding method, a blow molding method, etc. Among these, the extrusion molding method is preferred from the viewpoint of obtaining a film having excellent transparency, improved toughness, excellent handling properties, and an excellent balance between toughness, surface hardness, and rigidity. The temperature of the molten resin discharged from the extruder is preferably set to 160 to 270°C, more preferably 220 to 260°C.
[0155] Among the extrusion molding methods, the T-die method is preferred from the viewpoint of obtaining a film with good surface smoothness, good mirror gloss, and low haze. In this T-die method, it is preferable to sandwich the molten resin discharged from the T-die through an extruder, a gear pump, a polymer filter, and a mixer between two or more mirror-finished rolls or mirror-finished belts to form a film. When sandwiching between the mirror-finished rolls or mirror-finished belts, a bank may or may not be formed. The die has an automatic lip opening adjustment function, and the air gap is preferably 100 mm or less.
[0156] The mirror-finished roll or mirror-finished belt is preferably made of metal. As the mirror-finished roll, a metal rigid roll, a metal elastic roll, etc. can be used, and it is preferable to use a combination of a metal elastic roll and a metal rigid roll. In addition, the surface temperatures of both the mirror-finished roll or the mirror-finished belt are preferably 130°C or less. In addition, it is preferable that at least one of the pair of mirror-finished rolls or mirror-finished belts has a surface temperature of 60°C or more. By setting the surface temperature at such a level, the molten resin discharged from the extruder can be cooled at a rate faster than natural cooling, and a film with excellent surface smoothness and low haze can be easily produced. The linear pressure between the pair of rolls or belts is preferably 10 N / mm or more, more preferably 30 N / mm or more. The thickness of the unstretched film obtained by extrusion molding is preferably 10 to 300 μm. The haze of the film at a thickness of 100 μm is preferably 0.57% or less, more preferably 0.35% or less, and even more preferably 0.3% or less.
[0157] The unstretched film obtained as described above may be subjected to a stretching treatment. The stretching treatment increases the mechanical strength, and a film that is less likely to crack can be obtained. The stretching method is not particularly limited, and examples thereof include simultaneous biaxial stretching, sequential biaxial stretching, and tubular stretching. From the viewpoint of obtaining a film that can be uniformly stretched and has high strength, the lower limit of the temperature during stretching is a temperature 10°C higher than the glass transition temperature of the methacrylic resin or methacrylic resin composition, and the upper limit of the temperature during stretching is a temperature 40°C higher than the glass transition temperature of the methacrylic resin or methacrylic resin composition. The stretching is usually performed at 100 to 5000% / min. After stretching, heat setting can be performed to obtain a film with little thermal shrinkage. The thickness of the film after stretching is preferably 10 to 200 μm.
[0158] A functional layer may be provided on the surface of the film, which is one embodiment of the molded article of the present invention. Examples of the functional layer include a hard coat layer, an antiglare layer, an antireflection layer, an antisticking layer, a diffusion layer, an antiglare layer, an antistatic layer, an antifouling layer, and a slippery layer such as a fine particle layer.
[0159] In addition, it is preferable to provide an undercoat layer on at least one side of the film of the present invention in order to improve the adhesive strength with the functional layer or to improve the adhesive strength when laminated with other films via an adhesive or pressure-sensitive adhesive.
[0160] The methacrylic resin composition of the present invention is suitable as a molding material. The molded article of the present invention can be used as a member for various applications. Specific applications include, for example, signboard parts and marking films; display parts; lighting parts; interior parts; building parts; automobile interior parts, automobile exterior parts, and other transport-related parts; electronic equipment parts; medical equipment parts; equipment-related parts; optical parts; traffic-related parts; and other various surface materials.
[0161] A laminate can be obtained by laminating a layer containing the methacrylic resin composition of the present invention with another material (for example, a layer containing another thermoplastic copolymer). Examples of other materials used in the laminate include steel, plastic (for example, thermoplastic resin), wood, glass, etc. The laminate obtained by the present invention can be suitably used for wallpaper; automobile interior surface; automobile exterior surface such as bumper; mobile phone surface; furniture surface; personal computer surface; vending machine surface; bathroom surface such as bathtub, etc.
[0162] The film, which is one embodiment of the molded article of the present invention, is highly transparent and heat resistant, and therefore suitable for optical applications, and is particularly suitable for polarizer protection films, liquid crystal protection plates, surface materials for portable information terminals, display window protection films for portable information terminals, light guiding films, transparent conductive films with silver nanowires or carbon nanotubes applied to the surface, and front panels for various displays. The film of the present invention has high transparency and heat resistance, and can be used for applications other than optical applications, such as infrared cut films, crime prevention films, shatterproof films, decorative films, metal decorative films, shrink films, and in-mold label films.
[0163] When the film, which is one embodiment of the molded article of the present invention, is used as a polarizer protective film or a retardation film, it may be laminated on only one side of the polarizer film or on both sides. When laminating with the polarizer film, it can be laminated via an adhesive layer or a pressure-sensitive adhesive layer. As the polarizer film, a stretched film made of a polyvinyl alcohol resin and iodine can be used, and its thickness is preferably 1 to 100 μm. EXAMPLES
[0164] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0165] Measurements of physical properties were carried out by the following methods.
[0166] (Weight average molecular weight) The weight average molecular weight (Mw) of the resin obtained in the manufacturing example was determined by the GPC method (gas chromatography method). A sample solution was prepared by dissolving 4 mg of the resin to be measured in 5 ml of tetrahydrofuran. The temperature of the column oven was set to 40°C, and 20 μl of the sample solution was injected into the device at an eluent flow rate of 0.35 ml / min to measure the chromatogram. Ten standard polystyrene points with molecular weights in the range of 400 to 5,000,000 were measured by GPC, and a calibration curve showing the relationship between retention time and molecular weight was created. The Mw of the resin to be measured was determined based on this calibration curve. The value equivalent to the molecular weight of the standard polystyrene from the chromatogram measured by GPC (gel permeation chromatography) was taken as the molecular weight of the copolymer.
[0167] Equipment: Tosoh GPC equipment HLC-8320 Separation column: Tosoh Corporation's TSKguardcolum SuperHZ-H, TSKgel HZM-M, and TSKgel SuperHZ4000 connected in series Eluent: Tetrahydrofuran Eluent flow rate: 0.35 ml / min Column temperature: 40℃ Detection method: Refractive index (RI)
[0168] (Composition of each unit of precursor polymer) 13 The carbon ratios of the phenyl group of the α-methylstyrene unit, the methoxy group of the methyl methacrylate unit, and the carbonyl group of the maleic anhydride unit were determined by C-NMR, and the composition of each unit was calculated from this. The carbon ratio of the cyano group bonded to the carbon at the α-position was determined for copolymers containing acrylonitrile units, and the phenyl group bonded to the carbon at the α-position was determined for copolymers containing styrene units, and the composition of each unit was calculated from this. For copolymers containing methyl acrylate units, 13 In addition to C-NMR, the composition of each unit was calculated by determining the methyl acrylate unit using pyrolysis gas chromatography.
[0169] (glass transition temperature Tg) The resin obtained in the Production Examples was measured for its DSC curve in accordance with JIS K7121 using a differential scanning calorimeter (Shimadzu Corporation, DSC-50 (product number)) by heating it once to 250° C., then cooling it to room temperature, and then heating it from room temperature to 200° C. at a rate of 10° C. / min. The midpoint glass transition temperature determined from the DSC curve measured during the second heating was taken as the glass transition temperature in the present invention.
[0170] (Imide cyclization rate in methacrylic copolymer) 1 The copolymer was analyzed using H-NMR (Bruker Corporation; product name ULTRA SHIELD 400 PLUS). 1 H-NMR measurement was performed, and the imide cyclization rate (r) was calculated using the following formula from the area A of the peak derived from the O-CH3 group of methyl methacrylate around 3.5 to 3.8 ppm and the area B of the peak derived from the N-CH3 group of glutarimide and maleimide around 3.0 to 3.3 ppm.
[0171] Imidization rate (r) (%) = B / (A+B) x 100
[0172] (Glutarimide cyclization rate and maleimide cyclization rate in methacrylic copolymer) Using an infrared spectrophotometer, 1685 cm -1 The absorption intensity (Im) of the peak due to the carbonyl of maleimide in the vicinity and 1668 cm -1 The values calculated from the absorption intensity (Ig) of the nearby peak derived from the carbonyl of glutarimide and the imide cyclization rate (r) using the following formula were defined as the glutarimide cyclization rate (r1) and the maleimide cyclization rate (r2).
[0173] Glutarimide cyclization rate (r1) (%) = Ig / (Ig+Im) × r Maleimide cyclization rate (r2) (%) = Im / (Ig+Im) × r
[0174] (Amount of maleic anhydride in methacrylic copolymer) Using an infrared spectrophotometer, 1780 cm -1The absorption intensity of the peak due to the carbonyl of maleic anhydride in the vicinity and 1685 cm -1 The imidization ratio of maleic anhydride (R m ) was sought. 13 The amount of maleic anhydride (M) in the precursor polymer and the imidization ratio (R m ) The value calculated using the following formula was taken as the amount of maleic anhydride (m) in the resin.
[0175] Maleic anhydride amount (m) = M × (100 - R m ) / 100
[0176] (1% thermogravimetric reduction temperature) The methacrylic copolymers obtained in the Production Examples and the methacrylic resin compositions obtained in the Examples and Comparative Examples were heated at a rate of 10°C / min in a nitrogen atmosphere using a thermogravimetric analyzer (Shimadzu Corporation, TGA-50), and the temperature at which a 1% weight loss occurred was recorded as the 1% thermal weight loss temperature.
[0177] (Vicat softening temperature) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the methacrylic copolymers obtained in the manufacturing examples and the methacrylic resin compositions obtained in the examples and comparative examples were injection molded under the conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec to obtain rectangular test pieces with a thickness of 4 mm, a long side of 80 mm, and a short side of 10 mm. The Vicat softening temperature (VST) of each test piece was measured using an HDT tester 3M-2 manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with the method described in the B50 method of JIS K7206.
[0178] (Flexural modulus) The flexural modulus of the above-mentioned test piece having a thickness of 4 mm, a long side of 80 mm, and a short side of 10 mm was measured using a precision universal testing machine Autograph AG-IS5kN manufactured by Shimadzu Corporation in accordance with the method described in JIS K7171.
[0179] (saturated water absorption rate) A square test piece with a thickness of 3 mm and a side length of 50 mm was obtained by injection molding in the same manner as above. The test piece was vacuum dried for 24 hours under conditions of a temperature of 80°C and 5 mmHg. The test piece was then allowed to cool in a desiccator. The test piece was removed from the desiccator and its mass (initial mass) was immediately measured. The test piece was then immersed in distilled water at 23°C. The test piece was removed from the water, the water adhering to the surface was wiped off, and its mass was measured. Immersion in distilled water and mass measurement were repeated until there was no change in mass. The saturated water absorption rate was calculated from the mass (absorbed mass) when there was no change in mass and the initial mass using the following formula.
[0180] Saturated water absorption rate (%) = [(absorbed mass - initial mass) / initial mass] × 100
[0181] (Refractive Index) The methacrylic copolymer and elastomer obtained in the Production Examples were placed in a mold and heated at 230°C and 50 kg / cm 2 The specimen was pressed for 5 minutes at 40°C for 10 minutes to obtain a square specimen with a thickness of 3 mm and a side length of 50 mm. The end faces of the specimen were polished flat, and the refractive index was measured at 23°C using a KPR-20 made by Kalnew Optical Industries Co., Ltd.
[0182] (shock resistance) The above-mentioned test pieces having a thickness of 4 mm, a long side of 80 mm, and a short side of 10 mm were subjected to measurement of the unnotched Charpy impact strength in accordance with the method described in ISO 179-1. The following evaluations were made based on the obtained Charpy impact strength.
[0183] ◎: Charpy impact strength is 50kJ / m 2 End ◯: Charpy impact strength is 30kJ / m 2 More than 50kJ / m 2 less than ×: Charpy impact strength is 30 kJ / m 2 less than
[0184] (transparency) The above-mentioned square test pieces having a thickness of 3 mm and a side length of 50 mm were obtained. The haze of each test piece was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory) according to the method described in JIS K7361. The following evaluations were made based on the obtained haze.
[0185] ◎: Haze is less than 3% 〇: Haze is 3% or more and less than 5% ×: Haze is 5% or more
[0186] (weather resistance) The above-mentioned test pieces with a thickness of 4 mm, long side of 80 mm, and short side of 10 mm were subjected to accelerated exposure tests using a Sunshine Weather-O-Meter (black panel 63°C, spray cycle 18 minutes / 2 hours). The following evaluations were made based on the retention of Charpy impact strength after 500 hours.
[0187] ◎: Retention rate is 90% or more 〇: Retention rate is between 80% and 90% ×: Retention rate is less than 80%
[0188] (Moldability) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the methacrylic resin compositions obtained in the examples and comparative examples were injection molded under the conditions of a cylinder temperature of 280°C, a mold temperature of 75°C, and a molding cycle of 1 minute to produce flat plates with a length of 205 mm, a width of 160 mm, and a thickness of 0.5 mm. The ratio of the resin flow length (190 mm) to the thickness was 380. In addition, using a single screw extruder with a shaft diameter of 20 m, the methacrylic resin compositions obtained in the Examples and Comparative Examples were extruded through a 150 mm wide T-die at a resin temperature of 260°C to obtain a single layer film with a width of 100 mm and a thickness of 80 μm.
[0189] The appearance of the flat plate was visually observed. The moldability was judged based on the presence or absence of molding defects such as sink marks and silver spots. The appearance of the form was also visually observed. The moldability was judged based on the presence or absence of bubbles and gel particles.
[0190] ○: No sink marks on the molded product, no silver spots, no foaming in the film, no gel bubbling. No occurrence of ×: Sink marks or silver spots on molded products, or foaming or galling of the film. There is some lubrication
[0191] (Dimensional stability) The above-mentioned flat plate with a length of 205 mm, a width of 160 mm, and a thickness of 0.5 mm was placed in either (1) an incubator with a temperature of 60°C and a relative humidity of 90%, or (2) a thermostat with a temperature of 90°C and a relative humidity of 60%, and left in the air for 500 hours. The flat plate was removed from the incubator, and the lengthwise dimension was measured. The dimensional change rate from the lengthwise dimension before being placed in the incubator was calculated. Under both conditions (1) and (2), the dimensional change rate is 0.3% or less, and the rating is "○". If the dimensional change rate was more than 0.3% under either or both of conditions (1) and (2), the result was marked as "X."
[0192] <Examples of various materials> The precursor polymer (B) used was the material shown below. Precursor polymer (B): PLEXIGLAS hw55 manufactured by EVONIK (Mw=141,000, styrene / maleic anhydride / MMA=15% / 9% / 76%, Tg=122°C, 1% thermal weight loss temperature=320°C, saturated water absorption=2.2%, flexural modulus=3560MPa, refractive index=1.510)
[0193] (Precursor polymer) The precursor polymers Aa to Af in this production example were produced by the following method. Precursor polymers A-a to A-f The various purified monomers, 2,2'-azobis(2-methylpropionitrile) (AIBN) and n-octyl mercaptan (n-OM) were charged in the ratios shown in Table 1 into an autoclave equipped with a stirrer and dissolved uniformly to obtain polymerization raw materials.
[0194] The polymerization raw materials were continuously supplied from the autoclave at 1.5 kg / hr to a tank reactor controlled at the polymerization temperature shown in Table 1, and polymerization reaction was carried out by a bulk polymerization method with an average residence time of 2 to 3 hours, and a liquid containing a methacrylic copolymer was continuously discharged from the tank reactor. The polymerization conversion rate became the value shown in Table 1. Next, the liquid discharged from the reactor was heated to 230°C and supplied to a twin-screw extruder controlled at 240°C. In the twin-screw extruder, volatile matters mainly composed of unreacted monomers were separated and removed, and the methacrylic copolymer was extruded into strands. The strands were cut with a pelletizer to obtain a precursor polymer. The weight average molecular weight Mw, the ratio of each unit composition, the glass transition temperature Tg, the 1% thermal weight loss temperature, the water absorption rate, the bending modulus, and the refractive index of the obtained precursor polymer were measured. The results are shown in Table 1. In Table 1, the following abbreviations were used. MMA: Methyl methacrylate αMSt: α-methylstyrene Mah: Maleic anhydride MA: Methyl acrylate St: styrene AN: Acrylonitrile
[0195] (Methacrylic copolymer (A)) Manufacturing Example 1 The precursor polymer [Aa] was fed at 10 kg / hr to the transport section of a twin-screw extruder (manufactured by Japan Steel Works, Ltd.; product name TEX30α-77AW-3V) that was composed of a transport section, a melt-kneading section, a devolatilizing section, and a discharge section, and was set at a screw speed of 100 rpm and a temperature of 230°C. In the melt-kneading section in which a kneading block was installed, monomethylamine was injected from the additive supply port of the twin-screw extruder at a rate of 1.2 kg / hr, and the precursor polymer [Aa] was reacted with monomethylamine. The melt-kneading section was mostly composed of kneading disks, and seal elements were attached to both ends of the kneading disks. In the devolatilizing section, which was set at 37 Torr (about 5 kPa), by-products and excess monomethylamine were volatilized from the molten resin that had passed through the melt-kneading section, and discharged through multiple vents.
[0196] The molten resin extruded as a strand from the die at the end of the discharge section of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped methacrylic copolymer [A-1]. The methacrylic copolymer [A-1] had an imide cyclization rate (proportion of structural units (r)) of 20 wt%, with a glutarimide cyclization rate (r1) of 8 wt% and a maleimide cyclization rate (r2) of 12 wt%. The maleic anhydride (m) content was 3 wt%. The physical properties of the methacrylic copolymer [A-1] are shown in Table 1.
[0197] Manufacturing Example 2 Except for using the precursor polymer [Ab] instead of the precursor polymer [Aa], a methacrylic copolymer (A-2) was obtained in the same manner as in Production Example 1. The physical properties of the methacrylic copolymer (A-2) are shown in Table 1.
[0198] Production Example 3 A methacrylic copolymer (A-3) was obtained in the same manner as in Production Example 1, except that the precursor polymer (Ac) was used instead of the precursor polymer (Aa) and the amount of monomethylamine added was 1.5 kg / hr. The physical properties of the methacrylic copolymer (A-3) are shown in Table 1.
[0199] Production Example 4 A methacrylic copolymer (A-4) was obtained in the same manner as in Production Example 1, except that the precursor polymer (Ad) was used instead of the precursor polymer (Aa) and the amount of monomethylamine added was 1.8 kg / hr. The physical properties of the methacrylic copolymer (A-4) are shown in Table 1.
[0200] Production Example 5 Except for using the precursor polymer [Ae] instead of the precursor polymer [Aa], a methacrylic copolymer (A-5) was obtained in the same manner as in Production Example 1. The physical properties of the methacrylic copolymer (A-5) are shown in Table 1.
[0201] Production Example 6 A methacrylic copolymer (A-6) was obtained in the same manner as in Production Example 1, except that the precursor polymer (Af) was used instead of the precursor polymer (Aa) and the monomethylamine was added at a rate of 0.9 kg / hr. The physical properties of the methacrylic copolymer (A-6) are shown in Table 1.
[0202] Production Example 7 Except for adding monomethylamine at a rate of 0.3 kg / hr, a methacrylic copolymer (A-7) was obtained in the same manner as in Production Example 1. The physical properties of the methacrylic copolymer (A-7) are shown in Table 1.
[0203] Production Example 8 Except for adding monomethylamine at a rate of 4.0 kg / hr, a methacrylic copolymer (A-8) was obtained in the same manner as in Production Example 1. The physical properties of the methacrylic copolymer (A-8) are shown in Table 1.
[0204] Production Example 9 A methacrylic copolymer (A-9) was obtained in the same manner as in Production Example 1, except that the precursor polymer (B) was used instead of the precursor polymer (Aa) and the monomethylamine was added at a rate of 3.5 kg / hr. The physical properties of the methacrylic copolymer (A-9) are shown in Table 1.
[0205] [Table 1A]
[0206] [Table 1B]
[0207] (Elastomer (B)) Manufacturing Example 10 In a reactor equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a monomer inlet tube and a reflux condenser, 480 parts by mass of ion-exchanged water and 0.06 parts by mass of sodium polyoxyethylene tridecyl ether acetate were charged, and the inside of the reactor was fully replaced with nitrogen gas. Then, the inside temperature was set to 80°C. 112.1 parts by mass of a monomer mixture consisting of 47.0% by mass of methyl methacrylate, 4.9% by mass of methyl acrylate, 45.5% by mass of styrene, 1.4% by mass of allyl methacrylate and 1.2% by mass of n-octyl mercaptan and 0.78 parts by mass of sodium polyoxyethylene tridecyl ether acetate were added thereto. Then, 4.26 parts by mass of a 3% aqueous potassium persulfate solution was added, and the emulsion polymerization reaction was started at 80°C. After the temperature rise in the reactor due to the reaction heat subsided, the polymerization reaction was carried out for another 30 minutes so that the polymerization conversion rate was 98% or more.
[0208] Next, 5.32 parts by mass of 3% potassium persulfate aqueous solution was added to the reactor and stirred for 5 minutes. After that, 80.2 parts by mass of a monomer mixture consisting of 63.0% by mass of butyl acrylate, 36.0% by mass of Aronix M110 (paracumylphenol EO modified acrylate) and 1.0% by mass of allyl methacrylate and 0.377 parts by mass of sodium polyoxyethylene tridecyl ether acetate were continuously added dropwise over 60 minutes. After the dropwise addition, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more.
[0209] Next, 2.72 parts by mass of a 3% aqueous potassium persulfate solution was added to the reactor and stirred for 5 minutes. Then, 64.1 parts by mass of a monomer mixture consisting of 55.0% by mass of methyl methacrylate, 4.8% by mass of methyl acrylate, 40.0% by mass of benzyl methacrylate, and 0.2% by mass of n-octyl mercaptan was continuously dropped over 30 minutes. After the dropwise addition was completed, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more. By the above operations, a latex containing a multilayer copolymer elastomer was obtained. The latex was frozen and coagulated. Then, it was washed with water and dried to obtain a multilayer copolymer elastomer (B-1). The average particle size of the multilayer copolymer elastomer (B-1) was 0.23 μm and the refractive index was 1.517.
[0210] Manufacturing Example 11 In a reactor equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a monomer inlet tube and a reflux condenser, 480 parts by mass of ion-exchanged water and 0.06 parts by mass of sodium polyoxyethylene tridecyl ether acetate were charged, and the inside of the reactor was fully replaced with nitrogen gas. Then, the inside temperature was set to 80°C. 112.1 parts by mass of a monomer mixture consisting of 28.0% by mass of methyl methacrylate, 4.9% by mass of methyl acrylate, 64.5% by mass of styrene, 1.4% by mass of allyl methacrylate and 1.2% by mass of n-octyl mercaptan and 0.78 parts by mass of sodium polyoxyethylene tridecyl ether acetate were added thereto. Then, 4.26 parts by mass of a 3% aqueous potassium persulfate solution was added, and the emulsion polymerization reaction was started at 80°C. After the temperature rise in the reactor due to the reaction heat subsided, the polymerization reaction was continued for another 30 minutes so that the polymerization conversion rate was 98% or more.
[0211] Next, 5.32 parts by mass of 3% potassium persulfate aqueous solution was added to the reactor and stirred for 5 minutes. After that, 80.2 parts by mass of a monomer mixture consisting of 50.0% by mass of 2-ethylhexyl acrylate, 49.0% by mass of hydroxyethyl acrylate biphenyl ether (NK Ester A-LEN-10 manufactured by Shin-Nakamura Chemical Co., Ltd.), and 1.0% by mass of allyl methacrylate, and 0.377 parts by mass of polyoxyethylene tridecyl ether sodium acetate were continuously added dropwise over 60 minutes. After the dropwise addition, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more.
[0212] Next, 2.72 parts by mass of 3% potassium persulfate aqueous solution was added to the reactor and stirred for 5 minutes. Then, 64.1 parts by mass of a monomer mixture consisting of 38.0% by mass of methyl methacrylate, 4.8% by mass of methyl acrylate, 57.0% by mass of benzyl methacrylate, and 0.2% by mass of n-octyl mercaptan was continuously dropped over 30 minutes. After the dropwise addition, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more. By the above operations, a latex containing a multilayer copolymer elastomer was obtained. The latex was frozen and coagulated. Then, it was washed with water and dried to obtain a multilayer copolymer elastomer (B-2). The average particle size of the multilayer copolymer elastomer (B-2) was 0.23 μm and the refractive index was 1.534.
[0213] Manufacturing Example 12 In a reactor equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a monomer inlet tube and a reflux condenser, 480 parts by mass of ion-exchanged water and 0.3 parts by mass of sodium polyoxyethylene tridecyl ether acetate were charged, and the inside of the reactor was fully replaced with nitrogen gas. Then, the inside temperature was set to 80°C. 112.1 parts by mass of a monomer mixture consisting of 95.6% by mass of styrene and 4.4% by mass of divinylbenzene and 0.78 parts by mass of sodium polyoxyethylene tridecyl ether acetate were added thereto. Then, 4.26 parts by mass of a 3% aqueous potassium persulfate solution was added, and the emulsion polymerization reaction was started at 80°C. After the temperature rise in the reactor due to the reaction heat subsided, the polymerization reaction was continued for another 30 minutes so that the polymerization conversion rate was 98% or more.
[0214] Next, 5.32 parts by mass of 3% potassium persulfate aqueous solution was added to the reactor and stirred for 5 minutes. After that, 80.2 parts by mass of a monomer mixture consisting of 78.0% by mass of butyl acrylate, 20.0% by mass of styrene, and 2.0% by mass of allyl methacrylate and 0.377 parts by mass of sodium polyoxyethylene tridecyl ether acetate were continuously added dropwise over 60 minutes. After the dropwise addition, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more.
[0215] Next, 2.72 parts by mass of 3% potassium persulfate aqueous solution was added to the reactor and stirred for 5 minutes. Then, 64.1 parts by mass of a monomer mixture consisting of 38.0% by mass of methyl methacrylate, 4.8% by mass of methyl acrylate, 57.0% by mass of benzyl methacrylate, and 0.2% by mass of n-octyl mercaptan was continuously dropped over 30 minutes. After the dropwise addition, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more. By the above operations, a latex containing a multilayer copolymer elastomer was obtained. The latex was frozen and coagulated. Then, it was washed with water and dried to obtain a multilayer copolymer elastomer (B-3). The average particle size of the multilayer copolymer elastomer (B-3) was 0.13 μm and the refractive index was 1.535.
[0216] Manufacturing Example 13 In a pressure autoclave, 150 parts by mass of ion-exchanged water, 85 parts by mass of 1,3-butadiene, 15 parts by mass of styrene, 0.5 parts by mass of t-dodecyl mercaptan, 0.4 parts by mass of diisopropylbenzene hydroperoxide, 1.5 parts by mass of sodium pyrophosphate, 0.02 parts by mass of ferrous sulfate, 1.0 part by mass of dextrose, and 0.25 parts by mass of potassium oleate were charged and reacted with stirring at 50°C for 15 hours to produce a butadiene-based rubber polymerization latex.
[0217] 65 parts of the butadiene-based rubber polymerized latex (as solids) was charged into a flask, and after replacing with nitrogen, 10% aqueous solution of NaHCO31.2 parts by mass was added and stirred for 30 minutes. 0.25 parts of potassium oleate was added as a 7% aqueous solution to this liquid for stabilization. Then, 0.6 parts by mass of Rongalit was added, and the liquid temperature was kept at 70°C, and 35 parts by mass of a monomer mixture having the following composition was graft-polymerized to the butadiene-based rubber polymerized latex.
[0218] Per 100 parts by mass of the total graft monomer mixture, a mixture of 40 parts by mass of methyl methacrylate, 5 parts by mass of ethyl acrylate, and 0.1 parts by mass of t-butyl hydroperoxide (t-BH) was added dropwise over 1 hour as a monomer mixture for the first stage of grafting, and the mixture was polymerized by continuing stirring for 2 hours. Thereafter, a mixture of 40 parts by mass of styrene and 0.1 parts by mass of t-BH was added dropwise over 1 hour as a monomer mixture for the second stage of grafting, and the mixture was polymerized by continuing stirring for 2 hours. Finally, a mixture of 15 parts by mass of methyl methacrylate and 0.05 parts by mass of t-BH was added dropwise over 1 hour as a monomer mixture for the third stage of grafting, and the mixture was polymerized by continuing stirring for 2 hours to obtain a latex of multilayer copolymer elastomer (B-4).
[0219] 0.5 parts by mass of BHT was added to the obtained multi-layer copolymer elastomer (B-4) latex, and then 0.2% aqueous sulfuric acid solution was added to coagulate the multi-layer copolymer elastomer (B-4), which was then heat-treated and solidified at 90°C. The coagulated product was then washed with warm water and further dried to obtain a multi-layer copolymer elastomer (B-4) powder. The average particle size of the multi-layer copolymer elastomer (B-4) was 0.45 μm, and the refractive index was 1.527.
[0220] Manufacturing Example 14 In a reactor equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a monomer inlet tube and a reflux condenser, 480 parts by mass of ion-exchanged water and 0.3 parts by mass of sodium polyoxyethylene tridecyl ether acetate were charged, and the inside of the reactor was fully replaced with nitrogen gas. Then, the inside temperature was set to 80°C. 112.1 parts by mass of a monomer mixture consisting of 76.6% by mass of styrene, 16.0% by mass of methyl methacrylate, 4.9% by mass of methyl acrylate, 1.4% by mass of allyl methacrylate and 1.2% by mass of n-octyl mercaptan and 0.78 parts by mass of sodium polyoxyethylene tridecyl ether acetate were added thereto. Then, 4.26 parts by mass of a 3% aqueous potassium persulfate solution was added, and the emulsion polymerization reaction was started at 80°C. After the temperature rise in the reactor due to the reaction heat subsided, the polymerization reaction was continued for another 30 minutes so that the polymerization conversion rate was 98% or more.
[0221] Next, 5.32 parts by mass of 3% potassium persulfate aqueous solution was added to the reactor and stirred for 5 minutes. After that, 80.2 parts by mass of a monomer mixture consisting of 42.0% by mass of 2-ethylhexyl acrylate, 1.0% by mass of benzyl acrylate, 56.0% by mass of A-LEN-10 (NK Ester A-LEN-10 manufactured by Shin-Nakamura Chemical Co., Ltd.) and 1.0% by mass of allyl methacrylate, and 0.377 parts by mass of sodium polyoxyethylene tridecyl ether acetate were continuously added dropwise over 60 minutes. After the dropwise addition, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more.
[0222] Next, 2.72 parts by mass of 3% potassium persulfate aqueous solution was added to the reactor and stirred for 5 minutes. Then, 64.1 parts by mass of a monomer mixture consisting of 33.0% by mass of methyl methacrylate, 4.8% by mass of methyl acrylate, 62.0% by mass of benzyl methacrylate, and 0.2% by mass of n-octyl mercaptan was continuously dropped over 30 minutes. After the dropwise addition, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more. By the above operations, a latex containing a multilayer copolymer elastomer was obtained. The latex was frozen and coagulated. Then, it was washed with water and dried to obtain a multilayer copolymer elastomer (B-5). The average particle size of the multilayer copolymer elastomer (B-5) was 0.23 μm and the refractive index was 1.545.
[0223] Example 1 60 parts by mass of the methacrylic copolymer (A-1) and 40 parts by mass of the elastomer (B-1) were mixed together, melt-kneaded at 250°C in a twin-screw extruder with a shaft diameter of 20 mm, and extruded to obtain a methacrylic resin composition (C-1). The evaluation results are shown in Table 2.
[0224] Examples 2 to 9 A methacrylic resin composition was obtained in the same manner as in Example 1 except for the formulation shown in Table 2. The evaluation results are shown in Table 2.
[0225] [Table 2]
[0226] Comparative Examples 1 to 8 A methacrylic resin composition was obtained in the same manner as in Example 1 except for the formulation shown in Table 3. The evaluation results are shown in Table 3.
[0227] [Table 3]
[0228] As shown in Tables 1 to 3, the methacrylic resin composition of the present invention contains a methacrylic copolymer that has an excellent balance of heat resistance, low water absorption, thermal decomposition resistance, rigidity, and refractive index, and therefore maintains high heat resistance, low water absorption, high rigidity, and transparency even when an elastomer is added, and has good thermal stability. The methacrylic resin composition of the present invention can provide molded articles and films that are excellent in transparency, dimensional stability, moldability, and weather resistance.
Claims
1. A methacrylic resin composition comprising 51 to 99 mass% of a methacrylic copolymer (A) having 15 to 83 mass% of methyl methacrylate units, 7 to 35 mass% of α-methylstyrene units, 9.9 to 65 mass% of a structural unit (r) having at least two ring structures in the main chain selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, an N-substituted or unsubstituted glutarimide unit, and an N-substituted or unsubstituted maleimide unit, 0.1 to 20 mass% of a maleic anhydride unit (m), and 0 to 20 mass% of other vinyl monomer units (c) copolymerizable with methyl methacrylate, and 1 to 49 mass% of an elastomer (B), wherein the structural unit (r) comprises an N-substituted or unsubstituted glutarimide unit represented by formula (I) and an N-substituted or unsubstituted maleimide unit represented by formula (II), The elastomer (B) contains a multilayer copolymer elastomer having a methacrylic acid ester unit and an acrylic acid ester unit, the refractive index difference between the methacrylic copolymer (A) and the elastomer (B) is 0.01 or less; A methacrylic resin composition, in which the mass ratio, {100×(m) / (r)}, of a maleic anhydride unit (m) to a structural unit (r) having in its main chain at least two or more ring structures selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, an N-substituted or unsubstituted glutarimide unit, and an N-substituted or unsubstituted maleimide unit, is in the range of 10 to 30%. 【Chemistry 1】 (In formula (I), R 1 are each independently a hydrogen atom or a methyl group; R 2 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. 【Chemistry 2】 (In formula (II), R 3 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.
2. The methacrylic resin composition according to claim 1, wherein the other vinyl monomer unit (c) copolymerizable with the methyl methacrylate unit is formed of at least one monomer selected from the group consisting of an acrylic acid ester monomer (c-1), an aromatic vinyl monomer (c-2), and a vinyl cyanide monomer (c-3).
3. 3. The methacrylic resin composition according to claim 1, wherein the other vinyl monomer unit (c) copolymerizable with the methyl methacrylate unit is formed of at least one monomer selected from the group consisting of methyl acrylate, ethyl acrylate, styrene, and acrylonitrile.
4. 4. The methacrylic resin composition according to claim 1, wherein the refractive index of the methacrylic copolymer (A) is in the range of 1.500 to 1.
540.
5. 5. The methacrylic resin composition according to claim 1, wherein the average particle size of the multilayer copolymer elastomer is from 0.15 μm to 1.0 μm.
6. A molded article comprising the methacrylic resin composition according to any one of claims 1 to 5.
7. A film comprising the methacrylic resin composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Production of heat-resistant methacrylic resin
JP1985147417A
Production of heat-resistant methacrylate resin composition
JP1986151216A
Film for protecting polarizing film
JP1993119217A
Optical resin sheet
JP1994194501A
Acrylic resin film
JP2000178399A